9y+30+6+6y=13y-2y

Simple and best practice solution for 9y+30+6+6y=13y-2y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9y+30+6+6y=13y-2y equation:


Simplifying
9y + 30 + 6 + 6y = 13y + -2y

Reorder the terms:
30 + 6 + 9y + 6y = 13y + -2y

Combine like terms: 30 + 6 = 36
36 + 9y + 6y = 13y + -2y

Combine like terms: 9y + 6y = 15y
36 + 15y = 13y + -2y

Combine like terms: 13y + -2y = 11y
36 + 15y = 11y

Solving
36 + 15y = 11y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-11y' to each side of the equation.
36 + 15y + -11y = 11y + -11y

Combine like terms: 15y + -11y = 4y
36 + 4y = 11y + -11y

Combine like terms: 11y + -11y = 0
36 + 4y = 0

Add '-36' to each side of the equation.
36 + -36 + 4y = 0 + -36

Combine like terms: 36 + -36 = 0
0 + 4y = 0 + -36
4y = 0 + -36

Combine like terms: 0 + -36 = -36
4y = -36

Divide each side by '4'.
y = -9

Simplifying
y = -9

See similar equations:

| 7(x-2)-4(x+1)=-21 | | 6(2x-2)=45+5x | | 9y+3016+6y=13y-2y | | (v-2w-2)(v-4)=0 | | 2=200/w^2 | | 2x+8+x+1=0 | | 3(20x+50)=510 | | 5x+24(x-2)=184 | | -5x+40=6x-(70) | | 40x+7=40d+34 | | (27x^4)+3p=2p | | 2m+3=2m-3 | | 6r^3+2r^2-48r= | | 3y-7=80 | | H-3=12 | | (3v-w-2)(7v+6)=0 | | 4(x+2)+3(x-6)=-3 | | 5x-20=x-2.4 | | 5a/24÷1/12 | | 9x/-102/3 | | -5t=-35 | | ln[(x-9)/((x^(2)-81)^(5))]^((2)/(5)) | | (3x+21)=(6x+15) | | 7p+21+9=10p-10-3p | | X^4-5x^2=-6 | | 2x^2+4x=240 | | 3x+5y=102 | | X+25+3(x)=435 | | 4(x-5)=-1.2x-1.2 | | (2x+4)2=240 | | D-4/9=-1/12 | | 85-x=20+x |

Equations solver categories